2014
DOI: 10.1093/gbe/evu158
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and the Evolution of Darwin’s Finches

Abstract: The prevailing theory for the molecular basis of evolution involves genetic mutations that ultimately generate the heritable phenotypic variation on which natural selection acts. However, epigenetic transgenerational inheritance of phenotypic variation may also play an important role in evolutionary change. A growing number of studies have demonstrated the presence of epigenetic inheritance in a variety of different organisms that can persist for hundreds of generations. The possibility that epigenetic changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
119
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 58 publications
0
119
1
Order By: Relevance
“…In most wild animal populations examined to date, there has been an excess of DNA methylation variation relative to genetic variation (Massicotte et al, 2011;Mor an & P erez-Figueroa, 2011;Liu et al, 2012;Massicotte & Angers, 2012;Schrey et al, 2012;Liebl et al, 2013;Skinner et al, 2014;Wenzel & Piertney, 2014). First investigations into epigenetic variation in wild animal populations involved the salmonid, Oncorhynchus mykiss (Blouin et al, 2010).…”
Section: Population Epigenetics In the Wildmentioning
confidence: 99%
“…In most wild animal populations examined to date, there has been an excess of DNA methylation variation relative to genetic variation (Massicotte et al, 2011;Mor an & P erez-Figueroa, 2011;Liu et al, 2012;Massicotte & Angers, 2012;Schrey et al, 2012;Liebl et al, 2013;Skinner et al, 2014;Wenzel & Piertney, 2014). First investigations into epigenetic variation in wild animal populations involved the salmonid, Oncorhynchus mykiss (Blouin et al, 2010).…”
Section: Population Epigenetics In the Wildmentioning
confidence: 99%
“…Recent studies showed that methylation changes significantly contributed to the molecular basis of evolution (17,19). As a heritable epigenetic modification, methylation is believed to change (usually suppress) the transcription of genes by either altering the DNA structure or blocking the binding of transcriptional factors with DNA double-strand (21-24).…”
Section: Methylation Modification Of S Galili P53 As a Results Of Adamentioning
confidence: 99%
“…In addition to gene mutations, heritable epigenetic changes occur more frequently with paramount importance for adaptive evolution (17)(18)(19). We report here that the two contiguous Significance p53 has been shown to play important roles in environmental adaptive evolution.…”
mentioning
confidence: 80%
“…Epigenetic modifications can also survive the reprogramming events during fertilization and embryonic development, meaning that the DNA-methylome may be inherited over generations, leading to heritable epigenetic effects with markers that can stay for several generations [108,109]. Adding another layer of complexity to DNA methylation and its effect on genome is the potential mutagenic effects, a potential driver for evolution [110,111].…”
Section: Dna Methylationmentioning
confidence: 99%
“…Finally, CpG methylations are dependent on the genome, and SNP variation has the potential to both allow and deny DNA methylation at specific positions. A study of speciation in Darwin finches suggests that methylation patterns are not only inherited over a few generations, but transgenerationally over millennia and can be as important as genomic mutations [111]. Methylations are also suggested to have modified the genome, adding a new layer of complexity to epigenetic mechanisms, with epimutations moving to the stable realm of the genome [110].…”
Section: Gene Regulation and Domesticationmentioning
confidence: 99%